Mechanistic links between dietary protein and colorectal cancer: a mini review (Journal of Bangladesh Academy of Sciences, 2026)
Protein, an essential and indispensable component of our diet, provides amino acids for the development, growth, and maintenance of human body. There is growing concern that protein intake from certain sources and dietary patterns may be a triggering factor for colorectal cancer (CRC). However, the link between dietary protein intake and CRC remains unclear, and the researchers are working to unravel the connection and its implications. Although specific reports showed red and processed meat linked with an increased risk of CRC, several recent studies exhibited CRC inversely tied with certain types of amino acid intake. Accumulating data indicate that CRC development is multifactorial, including dietary and lifestyle factors, environmental factors, and genetic factors. Moreover, the development and progression of CRC depend on several disruptive molecular pathways. These findings collectively suggest that protein source, dietary diversity, and food preparation methods are more meaningful determinants of CRC risk than protein intake per sec. A balanced diet incorporating varied protein sources, along with fiber, vitamins, and minerals, remains the most evidencesupported strategy for CRC prevention. This article argues with the recent conceivable theories about CRC development, progression and its relationship with dietary protein and synthesizes current evidence on the relationship between dietary protein intake and CRC riskconcluding that no direct causal link exists between overall protein consumption and CRC development.J. Bangladesh Acad. Sci. 50(2); 157–167: June 2026